Boundaries of the international law and empire - Pitts, Jennifer, 1970- (Harvard University Press, 2018)
Against the dominant narrative first developed in the eighteenth century, which has held that international law had its origins in relations between sovereign European states that respected each other as free and equal, Boundaries of the International examines the deep entanglement of international law with European imperial expansion. As commercial relations with states such as the Ottoman and Empire and China intensified, European legal and political writers increasingly described them as anomalous and backward empires in a modern world of nation-states, even as European states were themselves expanding their imperial reach across the globe. The debate over the boundaries of international law included legal authorities from Vattel to Wheaton to Westlake but ranged well beyond professional jurists to political thinkers such as Montesquieu, Edmund Burke, and J.S. Mill, legislators and diplomats, colonial administrators and journalists. Dissident voices in this broader public debate insisted that European states had extensive legal obligations abroad. These critics provide valuable resources for the critical scrutiny of the political, economic, and legal inequalities that continue to afflict the global order.--